PERSEPSI BODY SHAME PADA SISWI SMA NEGERI SE-KOTA CIMAHI - Rima Irmayanti; Tita Rosita; Heris Hendriana (Jurnal Penelitian Bimbingan dan Konseling, 2020)
Adolescents are considered as individuals who are in the transition from childhood to adulthood. When teenagers are in transition, they talk a lot about themselves and their environment. Exploring outside that makes teenagers in the worst place in the conversation. Behaviors and sayings that are considered joking by teenagers, not a few that lead to a shy body but they themselves do not realize it. Thus it is necessary for research to reveal the perceptions of teenagers about body shame. The research methodology used is quantitative research methods, namely by using a questionnaire on female students of class X in the high school in Cimahi. Sampling is done using the Slovin technique. Slovin technique is used so that the sample used can be seen as a representative perception of female students of class X SMA in Cimahi City.The data obtained shows that the perception profile of the body is shy on female students of class X in the high school across Cimahi in a high position. This data can be interpreted about the general perception of female students of class X in the Cimahi City Senior High School to be more negative about body shame.